ANALISIS POTENSI KOMODITI KELAPA DALAM PENGEMBANGAN WILAYAH DI KABUPATEN PADANG PARIAMAN - yozi abdul rahman husen; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This research was conducted in Padang Pariaman Regency to : 1) Know which districts have coconut commudities as the basic economy sector in Padang Pariaman Regency 2) Know the potential competitiveness and level of coconut potential in each district in Padang Pariaman Regency 3) The contribution to know coconut in every district for business in Padang Pariaman Regency. This research method is descriptive with a quantitative approach. The data used are secondary data and primary data. The results of this study show the Location Quontient analysis of 17 District in Padang Pariaman Regency the basic economic sector there are 8 Districts. Based on the Shift Share analysis it show that the competitiveness of coconut has a rapidly growing category in 11 Districts and a developing category in 6 Districts. The Dynamic Location Quotient analysis shows that the current and future potential rates of coconut production are 5 Districts. The Class Typology analysis showed that there were 4 Districts that found the potential content of special coconut. The result of the superimposed MRP analysis showed 4 Districts with dominant contribution categories, 9 Districts with potential contribution and 4 Districts with saturated contribution.